In Vitro Digestibility and Fermentability of Complete Feeds as Affected by Vitamin Supplementation - Grewal, R.S.; Wadhwa, M.; Bakshi, M.P.S. (Indian Journal of Animal Nutrition, 2018)
The study was taken up to assess the effect of different vitamins on in vitro digestibility and fermentability of complete feeds at different metabolisable energy (ME) levels. Two iso-nitrogenous diets containing 10% (MME) and 20% (HME) higher ME than recommended (NRC, 2001) were formulated. Both thediets contained low rumen undegradable protein (LUDP; @ 24% of dietary CP). The complete feeds were supplemented with different vitamins either individually (niacin, biotin or vitamin E) or in different combinations (niacin and biotin; niacin and vitamin E; biotin and vitamin E; niacin, biotin and vitamin E) in 2 Ã—8 factorial design. Biotin, vitamin E and niacin were supplemented @ 1.33, 10.67 and 533 mg/kg DM of complete feed, respectively. The effect of ME levels in complete feed, irrespective of vitamins revealed that the net gasproduction (NGP), digestibility of true OM (P